2014
DOI: 10.1186/1751-0147-56-9
|View full text |Cite
|
Sign up to set email alerts
|

Udder health in beef cows and its association with calf growth

Abstract: BackgroundStudies outside the Nordic countries have indicated that subclinical mastitis (measured by milk somatic cell count or the California Mastitis Test), intramammary infections (IMI), or blind quarters in beef cows may have negative effects on beef calf growth. Knowledge on prevalence of such udder health problems in Swedish beef cows is scarce. Therefore, the main aim of this study was to investigate subclinical mastitis, IMI and udder conformation in a number of beef cow herds. Production of β-lactamas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…These authors highlighted the negative impact of cow mastitis on calf weaning weight. Moreover, Persson Waller et al [ 45 ] noted that beef cows with funnel-shaped teats or pendulous udders had a greater risk of mastitis, although they did not find any association between udder health and calf weaning weight. However, this might explain why our QTL detection for US highlighted this region as a major QTL.…”
Section: Discussionmentioning
confidence: 99%
“…These authors highlighted the negative impact of cow mastitis on calf weaning weight. Moreover, Persson Waller et al [ 45 ] noted that beef cows with funnel-shaped teats or pendulous udders had a greater risk of mastitis, although they did not find any association between udder health and calf weaning weight. However, this might explain why our QTL detection for US highlighted this region as a major QTL.…”
Section: Discussionmentioning
confidence: 99%
“…Udder structure: The structure of the udder also affects the susceptibility to the infection. Cattle with large funnel-shaped teats or pendular-shaped udder and blind quarters after calving are at greater risk of sub-clinical mastitis [49]. Other than that, teat size and teat to floor distance may also decrease the in vitro activity of leukocytes in milk hence increase the occurrence of IMIs [50].…”
Section: Host Factormentioning
confidence: 99%
“…Infection of the mammary gland resulting in mastitis is an important and well characterized disease of dairy cattle, such as the Holstein breed [ 1 ]. However, the incidence and severity of this disease in beef cattle has received little attention although two recent studies that examined mastitis prevalence in beef cows reported a moderate incidence with a surprising lack of Escherichia coli induced mastitis [ 2 , 3 ]. This pathogen is a major cause of mastitis in dairy animals and thus differences in susceptibility to E. coli infection may exist between dairy and beef breeds.…”
Section: Introductionmentioning
confidence: 99%